ANALISIS KESULITAN SISWA DALAM BELAJAR PEMECAHAN MASALAH MATA PELAJARAN IPS DI SD N 2 FAJAR AGUNG - Hidayat, Riski (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2020)
The research was aim to know ofstudents’ difficulties in studying problemsolving on social studies atSDN 2 Fajar Agung. The subjectin this research was sixthgrade atSDN 2 Fajar Agung in academic year of 2017/2018. The research methodwas qualitative research. The instrument ofthis research used observation dan interview. To analyze data,it used analyze thematic. The result showedthat the students’ difficulties in studying problem solving based on: (1) The teacher used conventional methodin learning process; (2) the curriculum used old curriculum; (3) The teacher gave test based on thebook; (4) The test only focusedto C1-C3 levels, (5) the teacher rarely usedmedia in learning process. Notonly the teacher and students, but also the students difficulties in studying problem solving based on:(1) Family, (2) Economic, (3) social and culture